Tantangan Hunian Berkelanjutan di Indonesia: Evaluasi Berdasarkan GBCI GREENSHIP HOMES 1.0 - Galieh Gunagama M.; Yumna Rana Naurah; Arganis Ellyza Putri Prabono (Universitas Muslim Indonesia, 2022)
Sustainability is a concept that today's planners need to understand. To achieve sustainability, the idea needs to be applied to the real world. Sustainability must start from a lifestyle that is also reflected in the residence occupied. GREENS HOMES (GH) from GBCI is an instrument to assess the application of the concept of sustainability in a house. The residential assessment conducted by students in Sustainable Architecture Courses in the UII Architecture Undergraduate Program can evaluate each home's condition. This activity is expected to build student awareness related to applying sustainability principles in their home. This study aims to look at the profile of occupancy in Indonesia and the challenges of sustainable houses judging by the results of the GH assessment. Based on the evaluation, it is known that the average house in Indonesia is ranked as Gold. Simultaneously, rating categories from the highest value to the lowest are IHC, EEC, ASD, MRC, BEM, and WAC. The biggest challenges of a sustainable house in Indonesia are the utilization of natural resources, obtaining and managing the goods used daily, the processing of consumables, and their impact on nature.